2005
DOI: 10.1007/s10165-005-0433-7
|View full text |Cite
|
Sign up to set email alerts
|

An external snapping hip caused by osteochondroma of the proximal femur

Abstract: We herein report the findings of a 17-year-old boy who suffered from a right external snapping hip, which was caused by an osteochondroma of the proximal femur. He has been asymptomatic since the excision of the tumor. This case shows a rare etiology in which an external snapping hip occurred between the iliotibal band and the osteochondroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Schaberg et al 5 have reported two cases of internal snapping hip due to proximal femur exostosis. Sanshiro et al 6 have reported a case of external snapping hip caused by exostosis of proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…Schaberg et al 5 have reported two cases of internal snapping hip due to proximal femur exostosis. Sanshiro et al 6 have reported a case of external snapping hip caused by exostosis of proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic effects of solitary exostoses of the proximal femur have been well described in cases involving trocha nteric bursitis, external snapping of the hip, and sciatic nerve compression, leading to either local treatment or surgical excision [1,6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al [9] described a snapping phenomenon during adduction and internal rotation of the hip in a case of osteochondroma of the proximal femur [9].…”
Section: Discussionmentioning
confidence: 99%